The Effect of Auditor Rotation and Auditor Reputation on Audit Quality in Companies Registered Banking Sub-Sectors on Bursa Efek Indonesia Period 2017-2019 - Siti Haliza; Rahima Br. Purba (Universitas Kristen Indonesia Toraja, 2022)
This research aims to analyze the effect of auditor rotation and auditor reputation on audit quality in banking sub-sector companies listed on the Indonesia Stock Exchange (BEI). Several previous studies regarding audit quality have shown different results. Therefore, other research needs to be conducted to retest theories about audit quality. The population of this research was 43 banking sub-sector companies. The sampling method used was a purposive sampling method so 24 sample companies were obtained for 3 years of observation (2017-2019) with 72 observations (observations). Research data was obtained from sample companies downloaded from the website Indonesia Stock Exchange. The data analysis techniques used are descriptive statistical analysis and logistic regression analysis. The data analysis process carried out first is descriptive statistical analysis, logistic regression analysis, and then hypothesis testing. The results of this research partially show that auditor rotation does not have a significant effect on audit quality. Meanwhile, the auditor's reputation partially has a significant effect on audit quality. The results of this research indicate that auditor rotation and auditor reputation simultaneously have a simultaneous effect on audit quality.